Impact of cost efficiency on bank capital and the cost of financial intermediation: Evidence from BRICS countries - Mohammed Mizanur Rahman; Badar Nadeem Ashraf; Changjun Zheng; Munni Begum (International Journal of Financial Studies, 2017)
Over last two decades, emerging and developing nations have desperately endeavored for efficient banking sectors. In this study, we argue that bank efficiency generates incentives that can impact banks' capital holdings and the cost of financial intermediation. Analyzing a panel dataset of 1190 banks from BRICS (Brazil, Russia, India, China, South Africa) countries over the period 2007-2015, we find robust evidence that more efficient banks hold higher capital and charge lower financial intermediation costs. In an extended sample over the period 2000-2015, we observe that cost efficiency had a marginal positive impact on bank capital during the global financial crisis of 2007-2009. We also observe that on average, banks increased the cost of financial intermediation during the crisis, however, greater efficiency helped banks to not charge higher intermediation costs. Our results imply the beneficial impact of bank efficiency for bank stability and real economy.
Keywords: D61; G21; G28; G01; 330; bank efficiency; the cost of financial intermediation; bank capital; financial crisis; emerging markets